CONFIRMATORY ANALYSIS OF CAREER MATURITY INSTRUMENTS AND GUIDANCE SERVICE IMPLICATIONS - Yahya, Ayu Intani; Nugraha, Agung; Sulistiana, Dewang (PT Altin Riset Publishing, 2025)
This study aims to develop a standard measurement tool that can be used to accurately measure the career maturity of high school students. The need for this measurement tool is motivated by the low level of understanding of students' career maturity, which is caused by the mismatch between the guidance and counseling services provided at schools and the actual needs of students. To achieve this objective, this study uses a quantitative approach with a confirmatory descriptive design. The research subjects were 918 eleventh-grade high school students in the northern region of Tasikmalaya District, with a sample of 707 students selected incidentally. This study is a continuation of the previous stage, which used exploratory factor analysis, and in this stage, the factor structure was confirmed through Confirmatory Factor Analysis (CFA). The CFA results indicate that the developed measurement tool has adequate goodness of fit values. During the confirmation process, there was a change in the indicator structure from 19 to 16 factors, as well as a reduction in the number of items from 65 to 62 relevant items. These findings indicate that the measurement tool produced is capable of providing a valid and reliable picture of the career maturity level of high school students. With the availability of this standardized measurement tool, it is hoped that guidance and counseling services in schools can be tailored more effectively and efficiently, ultimately enhancing students' career maturity. This study makes an important contribution to the development of educational intervention strategies focused on comprehensive career readiness for students.